Biosynthesis of the Macrocyclic Diterpene Casbene in Castor Bean (Ricinus communis L.) Seedlings : The Purification and Properties of Farnesyl Transferase from Elicited Seedlings - Dudley, Mark W. (1986)
Farnesyl transferase (farnesyl pyrophosphate: isopentenyl pyrophosphate farnesyl transferase; geranylgeranyl pyrophosphate synthetase) was purified at least 400-fold from extracts of castor bean (Ricinus communis L.) seedlings that were elicited by exposure for 10 h to Rhizopus stolonifer spores. The purified enzyme was free of isopentenyl pyrophosphate isomerase and phosphatase activities which interfere with prenyl transferase assays. The purified enzyme showed a broad optimum for farnesyl transfer between pH 8 and 9. The molecular weight of the enzyme was estimated to be 72,000 ± 3,000 from its behavior on a calibrated G-100 Sephadex molecular sieving column. Mg(2+) ion at 4 millimolar gave the greatest stimulation of activity; Mn(2+) ion gave a small stimulation at 0.5 millimolar, but was inhibitory at higher concentrations. Farnesyl pyrophosphate (K(m) = 0.5 micromolar) in combination with isopentenyl pyrophosphate (K(m) = 3.5 micromolar) was the most effective substrate for the production of geranylgeranyl pyrophosphate. Geranyl pyrophosphate (K(m) = 24 micromolar) could replace farnesyl pyrophosphate as the allylic pyrophosphate substrate, but dimethylallyl pyrophosphate was not utilized by the enzyme. One peak of farnesyl transferase activity (geranylgeranyl pyrophosphate synthetase) and two peaks of geranyl transferase activity (farnesyl pyrophosphate synthetases) from extracts of whole elicited seedlings were resolved by DEAE A-25 Sephadex sievorptive ion exchange chromatography. These results suggest that the pathway for geranylgeranyl pyrophosphate synthesis in elicited castor bean seedlings involves the successive actions of two enzymes—a geranyl transferase which utilizes dimethylallypyrophosphate and isopentenyl pyrophosphate as substrates and a farnesyl transferase which utilizes the farnesyl pyrophosphate produced in the first step and isopentenyl pyrophosphate as substrates.